The significance of at-risk or “prodromal” symptoms for bipolar-I disorder in children and adolescents - Hauser, Marta (2013)
BACKGROUND: While in the early identification and intervention of psychosis, specific instruments and risk criteria have been generated and validated, research into preventive strategies for bipolar-I disorder (BP-I) has only recently gained momentum. Since first signs of BP-I often start before adulthood, such efforts are especially important in the vulnerable pediatric population. METHODS: Narrative review of data regarding the presence and nature of potentially prodromal, i.e., sub-syndromal, symptoms prior to BP-I, defined by first-episode mania, focusing on pediatric patients. RESULTS: The possibility of early identification of youth at high-risk for BP is supported by retrospective studies of BP-I patients, and prospective studies of community samples, offspring of BP-I subjects, youth with depressive disorders, and patients at high-risk for psychosis or with BP-spectrum disorders without lifetime history of mania. These data provide essential insight into potential signs and symptoms that may enable pre-syndromal identification of BP-I in youth. However, except for offspring studies, broader prospective approaches that focus on youth at risk for BP-I and on developing specific interviews/rating scales and risk criteria are mostly missing, or in their early stage. CONCLUSIONS: More work is needed to determine valid clinical high-risk criteria, to distinguish risk factors, endophenotypes and comorbidities from specific prodromal symptomatology, and to develop phase-specific interventions that titrate the risk of intervention to the risk of transition to mania and to functional impairment or distress. Moreover, studies are needed that determine potential differences in prodromal symptoms and trajectories between children, adolescents and adults, and the best phase-specific interventions.